2014
DOI: 10.1007/s00300-014-1520-z
|View full text |Cite
|
Sign up to set email alerts
|

New species records and changes in abundance of waterfowl in northwest Greenland

Abstract: Breeding populations of Nearctic and Palearctic waterfowl have undergone significant changes in abundance and distribution over the past 50 years. The Avanersuaq District in northwest Greenland is home to an assemblage of waterfowl from both geographic areas; however, minimal historic or current information is available on species abundance. In 2008 and 2009, we conducted field surveys in Greenland from 76.00°to 77.35°N for breeding and non-breeding waterfowl and have collected anecdotal field notes of avian o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Recent changes in weather and climate have resulted in a northern range expansion for many avian species breeding in temperate zones in the Palearctic and Nearctic (Thomas & Lennon 1999;Hitch & Leberg 2007;Virkkala & Lehikoinen 2017;Dunn & Møller 2019). In the Arctic, a similar pattern has been observed, with birds extending their northern range limit and species that were once considered rare or vagrant now observed on an annual basis (Gaston & Woo 2008;Divoky 2011;Brommer et al 2012;Burnham et al 2012;Burnham et al 2014 ;Robinson et al 2019). More recently, focus has also included the transarctic movement of species, with some hypothesizing that decreasing Arctic sea ice will lead to increased movement among species, including seabirds, between the Pacific and Atlantic oceans (Vermeij & Roopnarine 2008;Post et al 2013;McKeon et al 2016;Clairbaux et al 2019).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Recent changes in weather and climate have resulted in a northern range expansion for many avian species breeding in temperate zones in the Palearctic and Nearctic (Thomas & Lennon 1999;Hitch & Leberg 2007;Virkkala & Lehikoinen 2017;Dunn & Møller 2019). In the Arctic, a similar pattern has been observed, with birds extending their northern range limit and species that were once considered rare or vagrant now observed on an annual basis (Gaston & Woo 2008;Divoky 2011;Brommer et al 2012;Burnham et al 2012;Burnham et al 2014 ;Robinson et al 2019). More recently, focus has also included the transarctic movement of species, with some hypothesizing that decreasing Arctic sea ice will lead to increased movement among species, including seabirds, between the Pacific and Atlantic oceans (Vermeij & Roopnarine 2008;Post et al 2013;McKeon et al 2016;Clairbaux et al 2019).…”
Section: Introductionmentioning
confidence: 55%
“…The Avanersuaq District in the High Arctic of north-west Greenland is home to the largest populations of breeding seabirds in Greenland (Boertmann et al 1996;see Burnham et al 2012 andBurnham et al 2014 for additional information about the area). For many avian species, this area represents the most northern extent of their breeding ranges (Boertmann et al 1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area has many small coastal islands and islets that are used by nesting waterfowl; Common Eider Somateria mollissima and Long-tailed Duck Clangula hyemalis frequently nest on the same islands as Arctic Terns. For additional descriptions of the study area, see Burnham et al ( , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Brommer et al (2012) documented a northern range shift of 0.81 km year -1 for northern boreal and Arctic nesting species in Finland from 1989 to 2006. In the High Arctic of northwest Greenland, Burnham et al (2014) suggested that a lengthened breeding window has led to an increase in the number of both new and rare waterfowl species. As a result, species which occupy overlapping niches are now competing for both nesting sites and prey.…”
Section: Thick-billed Murrementioning
confidence: 99%